The Influence of Tax Fairness Perception and Tax Knowledge on Tax Morale and Tax Compliance of MSME Taxpayers Partnered with Toko Basmallah - Abd Rohim; Heru Tjaraka (Eduvest - Journal of Universal Studies, 2025)
This study investigates the influence of tax fairness perception and tax knowledge on tax morale and tax compliance among MSME taxpayers partnered with TokoBASMALAH in East Java. Utilizing a quantitative research approach, data was collected through questionnaires distributed electronically. The results indicate that tax fairness perception and tax knowledge significantly enhance tax morale. Furthermore, tax morale positively affects tax compliance. However, tax fairness perception and tax knowledge do not have a direct significant impact on tax compliance. These findings highlight the importance of enhancing taxpayer education and perceptions of fairness to improve compliance rates among MSMEs.